Dietary Patterns and Cardiovascular Disease-Related Risks in Chinese Older Adults - Sun, Jing; Buys, Nicholas J.; Shen, Shu-Ying (Frontiers in Public Health, 2013)
Abstract Studies of Western populations demonstrate a relationship between dietary patterns and cardiovascular-related risk factors. Simiar research regarding Chinese populations is limited. This study explored the dietary patterns of Chinese older adults and their association with cardiovascular-related risk factors, including hypertension, obesity and metabolic syndrome. Data were collected using a 34-item Chinese food frequency questionnaire from 750 randomly selected older adults aged 50–88 who participated in the study in 2012. Factor analysis revealed four dietary patterns: a ‘traditional food pattern’, consisting of vegetable, fruit, rice, pork and fish; a ‘fast and processed food pattern’ consisting of fast or processed food products, sugar and confectionery; a ‘soybean, grain and flour food pattern’; and a ‘dairy, animal liver and other animal food pattern’. These patterns explained 17.48%, 9.52%, 5.51% and 4.80% of the variances in food intake, respectively. This study suggests that specific dietary patterns are evident in Chinese older adults. Moderate intake of ‘traditional Chinese food’ is associated with decreased blood pressure and cholesterol level. A dietary pattern rich in soybeans, grains, potatoes and flour is associated with reduced metabolic factors including reduced triglycerides, fasting glucose, waist circumference, and waist–hip ratio, and a high level of dairy, animal liver and other animal intake food pattern is associated with increased level of Body Mass Index. In conclusion, this study revealed identifiable dietary patterns among Chinese older adults that are significantly related to blood pressure and metabolic biomarkers. Further study using prospective cohort or intervention study should be used to confirm the association between dietary patterns and blood pressure and metabolic factors.